Communicative Competence as a Basic Element in the Development of the Pedagogical Culture of the Future Educator (Journal of Pedagogical Inventions and Practices, 2022)
the article presents ideas on the formation of the communicative ability of a teacher of a preschool educational organization. It has been revealed to scientists who have conducted research in this regard and their research.